QSAR Studies and Design of Some Tetracyclic 1,4-Benzothiazines as Antimicrobial Agents - Mor, S.; Nagoria, S.; Kumar, A.; Kumar, A.; Kaushik, C. P. (Drug Research, 2016)
A quantitative structure-activity relationship (QSAR) analysis has been performed on a series of 20 tetracyclic 1,4-benzothiazines (1a–1t) with antimicrobial activity to explain the observed biological activity trend on structural basis. Multiple linear regression (MLR) method was employed to establish statistically significant QSAR models. The developed models are robust, predictive and free from chance correlation with good fitting ability and sufficient generalizability. These studies revealed the dominance of WHIM parameters in describing antimicrobial activity of the title compounds. Further, design of some more active compounds is presented.
Keywords: antibacterial drugs; antifungal drugs; chemistry; WHIM parameters